An approach to forming dashboards for business processes state analysis - Kopp, A. M.; Orlovskyi, D. L.; Kuka, D. O. (НТУ "ХПІ", 2017)
There have been considered basic features of dashboards, their place and role in business process management concept, considered basic dashboards types, considered various recommendations of dashboards construction, and also considered basic visualization tools such as bar and line graphs, pie and scatter charts, bullet graphs and dials. An approach to formation of dashboards, used for the analysis of product supply business process state, has been proposed. Therefore, a set of performance indicators and a related system of scales have been defined. In order to solve the problem of dashboard design which means definition of number, type and place of visualization tools, mathematical models of unbounded and continuous knapsack problems have been applied. As a result of the proposed approach application, a prototype of a dashboard used for the analysis of product supply business process state has been developed.

Розглядаються основні особливості панелей індикаторів, їх місце та роль в управлінні бізнес-процесами, основні типи, різноманітні рекомендації з побудови, а також основні інструменти візуалізації. Пропонується підхід до формування панелей індикаторів, призначених для аналізу стану бізнес-процесів. Застосування запропонованого підходу розглядається для аналізу стану бізнес-процесу поставки продукції. В результаті застосування запропонованого підходу був розроблений прототип панелі індикаторів, призначеної для аналізу стану бізнес-процесу поставки продукції.
Про один підхід до формування панелей індикаторів для аналізу стану бізнес-процесів
Keywords: business process management; performance indicators; system of scales; BPM; управління бізнес-процесами; показники ефективності